2020
DOI: 10.1038/s41380-020-0646-3
|View full text |Cite
|
Sign up to set email alerts
|

Success and efficiency of phase 2/3 adjunctive trials for MDD funded by industry: a systematic review

Abstract: To review the success rate and efficiency of industry-sponsored phase 2/3 clinical trials for adjunctive therapies for antidepressant partial- and non-responders with major depressive disorder (MDD), a systematic search of Pubmed/Medline was conducted, in addition to abstracts of major psychiatric meeting held since 2010, of randomized, placebo-controlled adjunct oral pharmacotherapy trials in this patient population. Forty-six ( n = 33,900; 70 drug compactor arms) trials were pooled, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…While a large number of trials adopted the single‐blind placebo lead‐in period as a form of full enrichment of the trial in placebo non‐responders, this enrichment has failed to show benefits, as suggested by a meta‐analysis of 101 antidepressant trials 164 and recently replicated in a meta‐analysis of 347 antidepressant trials, of which 174 used a single‐blind placebo run‐in period 165 . Single‐blind placebo and open‐label medication lead‐in phases are inferior to other enrichment study designs, such as sequential parallel design 166 , and have longer duration and higher costs. Accounting for costs, sample size, and duration of trials, the sequential parallel design may to be more effective for phase 3 trials aiming to regulatory approval 166 .…”
Section: Trends Aimed To De‐risk Trial Programmes Of Novel Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a large number of trials adopted the single‐blind placebo lead‐in period as a form of full enrichment of the trial in placebo non‐responders, this enrichment has failed to show benefits, as suggested by a meta‐analysis of 101 antidepressant trials 164 and recently replicated in a meta‐analysis of 347 antidepressant trials, of which 174 used a single‐blind placebo run‐in period 165 . Single‐blind placebo and open‐label medication lead‐in phases are inferior to other enrichment study designs, such as sequential parallel design 166 , and have longer duration and higher costs. Accounting for costs, sample size, and duration of trials, the sequential parallel design may to be more effective for phase 3 trials aiming to regulatory approval 166 .…”
Section: Trends Aimed To De‐risk Trial Programmes Of Novel Agentsmentioning
confidence: 99%
“…Single‐blind placebo and open‐label medication lead‐in phases are inferior to other enrichment study designs, such as sequential parallel design 166 , and have longer duration and higher costs. Accounting for costs, sample size, and duration of trials, the sequential parallel design may to be more effective for phase 3 trials aiming to regulatory approval 166 .…”
Section: Trends Aimed To De‐risk Trial Programmes Of Novel Agentsmentioning
confidence: 99%
“…Despite the continuous efforts in developing new treatments, many drug candidates fail to advance in clinical trials due to efficacy or safety-related reasons [2, 3]. Drug repurposing refers to the process of identifying novel therapeutic effects of existing drugs, and represents a more efficient and cost-effective approach for identifying new therapeutic treatments [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, psychiatric medications are among the least successful, with a 6.3% ultimate likelihood of approval, success rates of 23.7% in Phase II and 55.7% in Phase III, and with substantially longer (about 2 years) Phase II and III development timelines than non-CNS indications [1,2]. In most cases, these failures are due to a lack of efficacy in demonstrating that active treatment signal separates from placebo and is a crucial reason several pharmaceutical companies have reduced or even closed their psychiatric research and development programs [3][4][5].…”
Section: Introductionmentioning
confidence: 99%